Implementing Higher-Order Thinking Skills Oriented Assessment in Islamic Religious Education - Rahmah, Syarifah; Ramlan; Wardhani, Nia; Alwiyah, Syarifah; Syarboini (LETIGES, 2026)
This study aims to critically examine the implementation of Higher Order Thinking Skills (HOTS)-oriented assessment in the first-semester final examination of Islamic Religious Education (IRE) at SD IT Anak Shaleh, with particular attention to the coherence between instructional planning, classroom enactment, and evaluative practices in fostering students’ higher-order cognitive capacities. Employing a qualitative descriptive design with a content analysis approach, the research collected data through non-participant observation, semi-structured interviews, and systematic document analysis of assessment instruments, syllabi, learning outcomes, and institutional archives. This study analysed data through iterative stages of reduction, categorical display, and inferential interpretation and ensured credibility through methodological and source triangulation, peer debriefing, and audit trail validation. The findings reveal that HOTS-based items predominantly target the L4–L6 cognitive levels of Bloom's Revised Taxonomy and align with the Merdeka Curriculum framework. The integration of the REACT pedagogical model (relating, experiencing, applying, communicating, and transferring) effectively enhanced contextual reasoning, analytical judgment, evaluative reflection, and creative synthesis across core IRE domains, including aqidah, fiqh, and Qur’an-Hadith. Quantitative score trends indicate a substantive improvement in student performance, increasing from an initial range of 50%–65% to 70%–82%, representing gains of 17%–22%, thereby substantiating the efficacy of HOTS-oriented assessment in activating advanced cognitive processes. Despite these contributions, the study faces limitations due to its single-site scope and reliance on qualitative interpretation, which may constrain generalisation. The originality of this research lies in its integrative analysis of learning objectives, instructional processes, and summative assessment within a unified HOTS framework at the primary level, positioning teachers as deliberate designers of cognitive architecture rather than mere evaluators.